PELAKSANAAN PEMBELAJARAN MENULIS CERITA PENDEK (STUDI KASUS DI KELAS XI SMK NEGERI 5 SURAKARTA) - Hafidah Fachrunisa; Budhi Setiawan; Ani Rakhmawati (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The purposes of the research are to describe and to explain the learning process of short-story writing based on Curriculum 2013 which includes teachers’ comprehension about Curriculum 2013, planning, implementation, and assessment based on the Curriculum 2013 and the constraints and efforts made to overcome the obstacles. The research used descriptive qualitative with a case study approach. The data resources in this research was obtained through observation, in-depth interviews, and documents analysis. Based on the results of the study, it was concluded that learning to write short stories needs to be evaluatedin order to increase the quality of learning process both from planning, implementation, and the assesment because there are still some obstacles in the implementation. This the Curriculum 2013 can be implemented in accordance with the concepts and rules have been made by the government and achieve the goal of education have been formulated.